Occlusion and hydration of scars: moisturizers versus silicone gels. Issue 2 (March 2023) - De Decker, Ignace; Hoeksema, Henk; Vanlerberghe, Els; Beeckman, Anse; Verbelen, Jozef; De Coninck, Petra; Speeckaert, Marijn M.; Blondeel, Phillip; Monstrey, Stan; Claes, Karel E.Y.
Abstract: Background: The mainstay of non-invasive scar management, consists of pressure therapy with customized pressure garments often combined with inlays, hydration by means of silicones and/or moisturizers as well as UV protection. It is generally accepted that scar dehydration resulting from impaired barrier function of the stratum corneum and expressed by raised trans epidermal water loss (TEWL) values, can lead to increased fibroblast activity and thereby hypertrophic scar formation. However, we have reached no consensus on exactly what optimal scar hydration is nor on barrier function repair: by means of silicone sheets, liquid silicone gels or moisturizers. Occlusive silicone sheets almost completely prevent TEWL and have been shown to be effective. Nevertheless, many important disadvantages due to excessive occlusion such as difficulties in applying the sheets exceeding 10–12 h, pruritus, irritation, and maceration of the skin are limiting factors for its use. To avoid these complications and to facilitate the application, liquid silicone gels were developed. Despite a reduced occlusion, various studies have shown that the effects are comparable to these of the silicone sheets. However, major limiting factors for general use are the long drying time, the shiny aspect after application, and the high cost especially when used for larger scars. Based on excellent clinical results after using three specific moisturizers for scar treatment in our patients, we wanted to investigate whether these moisturizers induce comparable occlusion and hydration compared to both each other and the widely recognized liquid silicone gels. We wanted to provide a more scientific basis for the kind of moisturizers that can be used as a full-fledged and cost-effective alternative to silicone gel. Methods: A total of 36 healthy volunteers participated in this study. Increased TEWL was created by inducing superficial abrasions by rigorous (20x) skin stripping with Corneofix® adhesive tape in squares of 4 cm². Three moisturizers and a fluid silicone gel were tested: DermaCress, Alhydran, Lipikar and BAP Scar Care silicone gel respectively. TEWL reducing capacities and both absolute (AAH) and cumulative (CAAH) absolute added hydration were assessed using a Tewameter® TM300 and a Corneometer® CM825 at different time points for up to 4 h after application. Results: We found an immediate TEWL increase in all the zones that underwent superficial abrasions by stripping. Controls remained stable over time, relative to the ambient condition. The mean percentage reduction (MPR) in TEWL kept increasing over time with Alhydran and DermaCress, reaching a maximum effect 4 h after application. Silicone gel reached maximal MPR almost immediately after application and only declined thereafter. The silicone gel never reached the minimal MPR of Alhydran or DermaCress. Hydration capacity assessed through CAAH as measured by the Corneometer was significantly less with silicone gel compared to the moisturizers. Compared to silicone gel Lipikar provided similar occlusion and the improvement in hydration was highly significant 4 h after application. Conclusion: Based on the results of both our previous research and this study it is clearly demonstrated that the occlusive and hydrative effect of fluid silicone gel is inferior to the moisturizers used in our center. Lipikar hydrates well but is less suitable for scar treatment due to the lack of occlusion. A well-balanced occlusion and hydration, in this study only provided by Alhydran and DermaCress, suggests that moisturizers can be used as a scar hydration therapy that replaces silicone products, is more cost-effective and has a more patient-friendly application. Highlights: Unbalanced moisturizers provide hydration without adequate occlusion and can paradoxically lead to skin dehydration. Well-balanced moisturizers provide strong occlusion and hydration of the stratum corneum with high longevity. Well-balanced moisturizers are an alternative to silicone products in scar prevention and management. DermaCress and Alhydran are examples of well-balanced moisturizers, making them ideal for scar hydration. The occlusive properties of fluid silicone gels might be overrated and they do not provide true skin barrier restoration.